A shift in content of the IS fundamentals course. (26th June 2007) - Wynekoop, Judy L.; Nakatani, Kazuo
In light of the recent discussion on whether Information Systems (IS) as a field should stay focused on its technology core, a survey of IS instructors was done to determine the current and growing emphases of the introductory fundamentals of IS courses. In general, topics relating to technology applied to business improvement are currently emphasised, while business topics are becoming increasingly important. Purely technological topics are currently seen as the least important and not gaining in importance.